ASSESSMENT OF THE PROPERTIES OF ASPHALT MODIFIED WITH USED TIRES - Olufikayo Aderinlewo (Civil Engineering Journal, 2017)
This study investigates the properties of asphalt mix modified with ground tire. The ground tire was introduced into the asphalt in a melted form at varying percentages of 2%, 4%, 6%, 8% and 10% by weight of the asphalt. The properties of the asphalt mixed with the ground tire were then obtained through penetration, softening point, flash and fire point and ductility tests. These properties were then compared with those of the control asphalt to determine the effectiveness of the ground tire in improving the asphalt properties. The results showed that the ground tire additive improved the asphalt properties considerably.